Linking Food Security, Migration and Development. (16th June 2013) - Crush, Jonathan
Abstract: The issue of food security is strikingly absent from current debates about the relationship between migration and development. The current international food security agenda displays a similar disregard for migration. There thus appears to be a massive disconnect between these two global development agendas. The reasons are hard to understand since the connections between migration and food security seem obvious. This article addresses possible reasons for the disconnect and then presents and discusses the implications for linking migration and food security of a recent survey in 11 African cities. The results show a consistent pattern of difference between urban migrant and non‐migrant households in relation to levels of food insecurity, sources of income, food procurement strategies, and participation in urban agriculture. This article therefore seeks to initiate a conversation between the separate worlds of migration and development on the one side, and food security on the other.